ANALYSIS OF HUMAN RELATIONS AND WORK LIFE BALANCE ON THE PERFORMANCE OF ONLINE TRANSPORTATION DRIVERS IN BERAU DISTRICT - Purwoko, Agus (International Conference On Economics Business Management And Accounting (ICOEMA), 2023)
This study aims to determine: (1) the human relations variable partially affects performance, (2) the work life balance variable partially affects performance, (3) the human relations and work life balance variables simultaneously affect the performance of district online transportation drivers Berau. This research was conducted in a survey of online transportation drivers in Berau district. Data collection was carried out using the interview method, namely giving questionnaires to online transportation drivers in Berau district, and the analytical tool used was multiple linear regression with the help of SPSS. The research hypothesis suggests that (1) the human relations variable partially affects performance, (2) the work life balance variable partially affects performance.